Synthesis and Electrochemical Performance of Polyacrylonitrile Carbon Nanostructure Microspheres for Supercapacitor Application. (11th August 2015) - Ma, Mimgjie; Zhang, Chao; Huang, Guangxu; Xing, Baolin; Duan, Yuling; Wang, Xiaojiao; Yang, Zhengpeng; Zhang, Chuanxiang
Abstract : Polyacrylonitrile (PAN) carbon nanostructure microspheres (CNM) with the average particle size of 200 nm were prepared in the range of 500 to 800°C. The precursors of CNM were obtained through soap-free emulsion polymerization followed by freeze drying, oxidative stabilization, and half-carbonization. KOH was employed as the activation agent of the precursor material, and the ratio between KOH and the precursor was selected as 2 : 1. The element content, pore structure, nitrogen-containing functional groups, and microstructure characterization were characterized via elemental analysis, N2 adsorption at low temperature, X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), and transmission electron microscopy (TEM), and the electrochemical properties were examined as well. The results revealed that the CNM displayed specific surface area as high as 2134 m 2 /g and the total pore volume could reach 2.01 cm 3 /g when the activation temperature was 700°C. Furthermore, its specific capacitance in 3 M KOH and 1 M organic electrolyte could reach 311 F/g and 179 F/g, respectively. And, also, abundant functional groups of N-5 and N-6 were rich in the surface of the material, which could cause Faraday reaction and got the increasing specific capacitance via improvement of the wettability of the electrode material.